TURIZM TARAWÍNÍŃ ZAMANAGÓY SOCIAL-EKONOMIKALÍQ RAWAJLANÍWDAǴÍ TUTQAN ORNÍ HÁM ÁHMIYETI - Turǵanbaev, Dawranbek Nietbay ulı (ILIM hám JÁMIYET, 2026)
This research article comprehensively analyzes the role and importance of the tourism industry in the context of modern socioeconomic development. The study explores the theoretical foundations of the concept of tourism, the main types of tourism, and their impact on various economic sectors.